Odpowiedź :
Odpowiedź:
5 1/2 * 2 2/11 - 3 2/3 =
[tex]\frac{11}{2}*\frac{24}{11}-3\frac{2}{3}=[/tex]
[tex]12-3\frac{2}{3}=[/tex][tex]8\frac{1}{3}[/tex]
1 3/4 - 6 1/2 * 1/6 =
[tex]1\frac{3}{4}-\frac{13}{2}*\frac{1}{6}=[/tex]
[tex]\frac{21}{12}-\frac{13}{12}=\frac{8}{12}=\frac{2}{3}[/tex]
1 1/2 : 3/8 + 7 =
[tex]\frac{3}{2}*\frac{8}{3}+7=[/tex]
[tex]4+7=11[/tex]
1 4/5 : (8 13/25 - 1 1/2 ) =
[tex]\frac{9}{5}:(8\frac{26}{50}-1\frac{25}{50})=[/tex]
[tex]\frac{9}{5}*7\frac{1}{50}=[/tex]
[tex]\frac{9}{5}*\frac{351}{50}=\frac{10}{39}[/tex]
Szczegółowe wyjaśnienie:
Odpowiedź:
5 1/2•2 2/11-3 2/3=11/2•24/11-3 2/3=12-3 2/3=8 1/3
1 3/4-6 1/2•1/6=1 3/4-13/2•1/6=1 3/4-13/12=
=1 3/4-1 1/12=1 9/12-1 1/12=8/12=2/3
1 1/2:3/8+7=3/2•8/3+7=4+7=11
1 4/5:(8 13/25-1 1/2)=9/5:(8 26/50-1 25/50)=
=9/5:7 1/50=9/5:351/50=9/5•50/351=10/39